Patterns of injury following equine trauma: a non-trauma centre experience. Issue 2 (May 2021) - Dick, Lachlan; Yule, Michael; Green, James; Young, Jamie
Introduction: Horse riding carries risk of injury which can result in fatality. The majority of published literature describes major trauma centre experience. We aimed to characterise injury patterns following equine trauma at a Scottish district general hospital. Methods: A retrospective review of admissions following equine trauma was undertaken from 2014 to 2019. Mechanism and nature of injuries were noted. Patient management and outcomes were recorded and analysed to determine correlation. Results: Of the 162 patients identified, 121 (74.7 per cent) were female. The commonest mechanism and injury sustained were falling from a horse (86.4 per cent) and head injury (17.9 per cent) respectively. Forty-four (27.2 per cent) had multiple injuries identified. Being crushed or kicked resulted in more abdominal visceral injuries (22.7 vs 0.7 per cent, p = <0.05) and ITU admissions (18.2 vs 6.4 per cent, p = 0.06) when compared with falling from alone. Eight (4.9 per cent) required transfer to a major trauma centre and 30-day mortality was 0.6 per cent. Conclusion: Although variable, injuries following equine trauma can be life threatening. Increased awareness and development of safety legislation is needed. In addition, research could be directed at assessing functional outcomes given the large number of orthopaedic injuries.